Implementation of a STEM-Based Project-Based Learning Model to Improve Students' Science Process Skills on Alternative Energy Material - Batrisyia, Saskia Quraruaini; Suwarna, Irma Rahma; Liliawati, Winny (Jurnal Penelitian Pembelajaran Fisika, 2024)
Science process skills are skills that students must have in learning Physics because students are required to be able to apply scientific methods and knowledge and develop the knowledge skills they already have, so that science process skills are needed by students to face the real world which is dominated by technology and science. The purpose of this study is to ascertain how students' science process abilities in studying physics are affected by a STEM (science, technology, engineering, and mathematics) project-based learning approach. The study's sample was selected through the use of purposeful sampling. The sample consisted of thirty-four X grade students from a public high school in Bandung City. Formative pretest-posttest testing was used in this study as part of a quantitative pre-experiment methodology. Twelve multiple-choice questions were utilized in a formative evaluation of the abilities of the science process to collect research data. The results revealed that the moderate group had an N-Gain score of 0.61. A high category for observing and classifying indicators and a medium category for forecasting, measuring, drawing conclusions, and presenting indicators are used to categorize the improvement in science process skills indicators. Thus, the STEM-based learning model can improve students' science process skills.